2015
DOI: 10.11613/bm.2015.015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Bland Altman analysis

Abstract: In a contemporary clinical laboratory it is very common to have to assess the agreement between two quantitative methods of measurement. The correct statistical approach to assess this degree of agreement is not obvious. Correlation and regression studies are frequently proposed. However, correlation studies the relationship between one variable and another, not the differences, and it is not recommended as a method for assessing the comparability between methods.
In 1983 Altman and Bland (B&A) proposed an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
2,229
3
51

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 3,001 publications
(2,322 citation statements)
references
References 16 publications
39
2,229
3
51
Order By: Relevance
“…We used the Bland–Altman analysis to evaluate the mean, standard deviation (SD), and upper/lower reproducibility limits (URL/LRL), Eqs. (4) and (5), for radiomic features in response to variation in each testing parameter 54, 55, 56URL=Mean+(1.96×SD) LRL=Mean(1.96×SD) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Bland–Altman analysis to evaluate the mean, standard deviation (SD), and upper/lower reproducibility limits (URL/LRL), Eqs. (4) and (5), for radiomic features in response to variation in each testing parameter 54, 55, 56URL=Mean+(1.96×SD) LRL=Mean(1.96×SD) …”
Section: Methodsmentioning
confidence: 99%
“…We considered any feature below the low level as nonreproducible (NR). We based this approach on methods reported in several clinical studies 41, 53, 54, 55. Also, Galavis et al36 used a similar scale to categorize the features based on their variation, and Tixier et al37 indicated that such limits were referenced to previously defined reproducibility limits for standard uptake values.…”
Section: Methodsmentioning
confidence: 99%
“…It simply quantifies the bias and a range of agreement, within which 95 % of the differences between one measurement and the other are included [13]. However, there is no clinical evidence about clinical acceptable margin to evaluate the results.…”
Section: Discussionmentioning
confidence: 99%
“…A Bland-Altman plot was graphed [11,12]. The inferior and superior limits of agreement [LOA] were determined.…”
Section: Statisticsmentioning
confidence: 99%